NOD-Like Receptors in Lung Diseases - Chaput, Catherine; Sander, Leif E.; Suttorp, Norbert; Opitz, Bastian (Frontiers in Immunology, 2013)
The lung is a particularly vulnerable organ at the interface of the body and the exterior environment. It is constantly exposed to microbes and particles by inhalation. The innate immune system needs to react promptly and adequately to potential dangers posed by these microbes and particles, while at the same time avoiding extensive tissue damage. NOD-like receptors (NLRs) represent a group of key sensors for microbes and damage in the lung. As such they are important players in various infectious as well as acute and chronic sterile inflammatory diseases, such as pneumonia, chronic obstructive lung disease (COPD), acute lung injury/ARDS, pneumoconiosis and asthma. Activation of most known NLRs leads to the production and release of pro-inflammatory cytokines, and/or to the induction of cell death. We will review NLR functions in the lung during infection and sterile inflammation.